Comparative study of newly-bred black locust clones with regard to photosynthetic rate and water use efficiency: early evaluation - Ábri, Tamás; Csajbók, József (Acta Agraria Debreceniensis, 2023)
Black locust (Robinia pseudoacacia L.) is one of the most important tree species in Hungary, due to its positive economic impacts. Research to increase its yield, improve its stem quality and enhance its drought tolerance has been ongoing since the 1960s. Of the current research works in this field, the clone trial of the Forest Research Institute, University of Sopron, established in 2020 in the Nyírség region, is worth highlighting. In this experiment 4 newly-bred clones and a state-approved black locust cultivar (’Üllői’) are being tested. In the summer of 2022, ‘on site’ measurements of assimilation parameters – net assimilation (An), transpiration (Tr) – were carried out using the LI-6800 portable photosynthesis system. From the data obtained, the water use efficiency (WUE) was calculated. The results of the statistical analysis (Kruskal-Wallis H test) have shown significant differences (p < 0.05) between the clones for all three parameters (An, Tr, WUE) tested. The NK2 clone has performed the highest value for all the parameters studied. However, no significant differences were found between clones NK2 and PL040 for Tr or between NK2 and control (’Üllői’) for WUE. Studies of this kind contribute to the improvement of black locust growing through the production and selection of cultivars, which are relatively resistant to the negative effects (drought) of climate change.